MODEL KEBIJAKAN DALAM PENGENDALIAN BENCANA KEBAKARAN HUTAN DAN LAHAN - Alan Dwi Wibowo; Riswan; Rahmawati (Jurnal Sains dan Teknologi, 2022)
Forest and land fire disasters in Indonesia have started to become a hot topic of discussion in the last decade. Not only attract domestic attention, international organizations also paid attention to the incidence of this wildfire. The widespread wildfire is considered a serious threat by Indonesia government. This disaster completely has a negative impact on economy, health, environment, social and cultural aspect. Indonesia has received a lot of criticism in its efforts to control the wildfire disaster. Indonesia is required to present the right policy formulation to control this disaster. This study aims to provide policy alternatives that are implementable and effective in controlling wildfire disasters in Indonesia. The dynamic systems modeling approach was used in this study with a mean absolute percentage error of 8.65%. It is predicted that there will be another spike of hotspots in 2023. Suppressive and preventive strategies have been used as leveraging variables in controlling fire disasters. The combination of these two strategies with the dominance of a preventive strategy has proved to be quite effective in controlling the chance of catastrophic forest and land wildfires in the next few years.